C/EBPα Epigenetically Modulates TFF1 Expression via mC-6 Methylation in the Jejunum Inflammation Induced by a Porcine Coronavirus - Qu, Huan; Zong, Qiufang; Wang, Haifei; Wu, Shenglong; Cai, Demin; Bao, Wenbin (Frontiers in Immunology, 2022)
Porcine epidemic diarrhea virus (PEDV) is an emerging coronavirus, which causes acute diarrhea and destroys gastrointestinal barrier function in neonatal pigs. Trefoil factor 1 (TFF1) is a protective peptide for maintaining the integrity of gastrointestinal mucosa and reducing intestinal inflammation. However, its role in protecting intestinal epithelium against PEDV infection is still unclear. In this study, we discovered that TFF1 expression was activated in the jejunum of pigs with PEDV infection and TFF1 is required for the growth of porcine intestinal epithelial cell. For instance, inhibited cell proliferation and cell arrest were observed when TFF1 is genetic knocked-out using CRISPR-Cas9. Additionally, TFF1 depletion increased viral copy number and PEDV titer, along with the elevated genes involving in antiviral and inflammatory cytokines. The decreased TFF1 mRNA expression is in line with hypermethylation on the gene promoter. Notably, the strong interactions of protein-DNA complexes containing CCAAT motif significantly increased C/EBPα accessibility, whereas hypermethylation of mC-6 loci decreased C/EBPα binding occupancies in TFF1 promoter. This may be attributed to the enhanced mC-6 loci methylation, thus TFF1 hypermethylation diminished the binding efficiency of C/EBPα. Overall, our findings show that PEDV triggers the C/EBPα-mediated epigenetic regulation of TFF1 in intestine epithelium and facilitates host resistance to PEDV and other Coronavirus infection.